Features of State of Economy of Nogai Societies of North Caucasus in 19th — Early 20th Centuries - A. T. Dzhumagulova (Научный диалог)
The relevance of the study is due to the insufficiently studied and fragmentary coverage of the problem of development and regression of the Nogai societies of the North Caucasus traditional economic sectors in the 19th — early 20th centuries. The novelty of the study lies in the fact that in this study, the situation of the main economic sectors of the Nogais (horse breeding, sheep breeding, cattle breeding) is considered in a historical retrospective in the relationship of state policy aimed at transferring the nomadic Nogais to a settled state, reducing pasture spaces and natural and climatic phenomena and factors that caused emergency situations in the economy of nomadic societies. As a result of this impoverished pastoralists were forced to switch to a semi-nomadic or sedentary form of life. The author draws attention to the fact that in the conditions of a shortage of water sources and extreme (abnormally cold and abnormally hot) weather, the extensive nomadic pastoralism of the Nogais in the 19th and early 20th centuries experienced a serious crisis. It is concluded that at the end of the 19th — beginning of the 20th centuries, the Nogais of the North Caucasus were undergoing a process of decomposition and decline of nomadic pastoralism. It is noted that herd forms of cattle breeding are gradually being replaced by domestic types, permanent dwellings appear, agriculture is developing